Pengaruh Asimetri Informasi Dan Ketaatan Aturan Akuntansi Terhadap Kecenderungan Kecurangan Akuntansi Di Pemerintahan Kota Payakumbuh - Rifandra Adwitya; Vita Fitria Sari (Universitas Negeri Padang, 2020)
Accounting fraud occurred in the form of misstatement of financial statements, abuse of authority by rejecting information by accounting management in the government. This study aims to determine the effect of asymmetric information and compliance with accounting rules on accounting fraud in the Payakumbuh city government. The sample of 124 respondents was determined by proportional stratified random sampling consisting of direct or indirect Echelon II, III and IV accounting managers. Data were analyzed using multiple regression formulas with the help of the SPSS application for windows. This study concludes that information asymmetry and significant positive influence means increasing the likelihood of fraud. Whereas adherence to accounting rules does not affect accounting fraud due to lack of rewards and penalties for accounting managers from implementing the established rules.